Study of Laemostenus species across Zagros and Central zone of Iran, with the description of seven new cavernicolous species and notes on subgenus Iranosphodrus (Coleoptera: Carabidae: Sphodrini) - Tahami, Mohadeseh Sadat; Muilwijk, Jan; Lohaj, Roman; Sadeghi, Saber (Zootaxa, 2017)
The species belonging to the Sphodrine genus Laemostenus Bonelli, 1810 from central and southern Zagros Mts. and central zones of Iran were studied. Two new species-groups of the subgenus Antisphodrus Schaufuss, 1865 are proposed, and seven new species belonging to subgenera Antisphodrus Schaufuss, 1865 and Iranosphodrus Lohaj & Casale, 2011 are described. Morphological characters of the habitus and shape of male genitalia were used to delimit the species. New species of subgenus Antisphodrus are: L. (A.) zagrosensis sp. nov. and L. (A.) speleophilus sp. nov. from Chaharmahal and Bakhtiari province, and L. (A.) farsicus sp. nov. from Fars province (zagrosensis species-group); Laemostenus (A) zakariyiensis sp. nov. from Fars province (aequalis species-group), and L. (A.) shirazensis sp. nov. from Fars province (glasunowi species-group).  Based on the newly collected material, the subgenus Iranosphodrus is redefined and two new species from Yazd province are described: L.(I.) yazdensis sp. nov. and L.(I.) troglophilus sp. nov. An identification key for the Laemostenus species of the studied area is provided, and a check list for Iranian representatives of subgenera Antisphodrus and Iranosphodrus are given.